1991
DOI: 10.1091/mbc.2.11.915
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ca2+ influx during mitosis: Ca2+ influx and depletion of intracellular Ca2+ stores are coupled in interphase but not mitosis.

Abstract: Activation of a wide variety of membrane receptors leads to a sustained elevation of intracellular Ca2+ ([Ca2+]i) that is pivotal to subsequent cell responses. In general, in nonexcitable cells this elevation of [Ca2+]i results from two sources: an initial release of Ca2+ from intracellular stores followed by an influx of extracellular Ca2+. These two phases, release from intracellular stores and Ca2+ influx, are generally coupled: stimulation of influx is coordinated with depletion of Ca2+ from stores, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 36 publications
5
62
0
Order By: Relevance
“…SOCE is inhibited as the oocyte commits to meiosis (12), and MPF activation is sufficient for SOCE inactivation (12). As is the case in Xenopus eggs, SOCE inactivates during mitosis of mammalian cells (13,18). Here we show that SOCE inactivation during meiosis is the result of Orai1 internalization and to the inability of STIM1 to cluster in response to store depletion.…”
mentioning
confidence: 50%
See 2 more Smart Citations
“…SOCE is inhibited as the oocyte commits to meiosis (12), and MPF activation is sufficient for SOCE inactivation (12). As is the case in Xenopus eggs, SOCE inactivates during mitosis of mammalian cells (13,18). Here we show that SOCE inactivation during meiosis is the result of Orai1 internalization and to the inability of STIM1 to cluster in response to store depletion.…”
mentioning
confidence: 50%
“…Inactivation of Ca 2ϩ influx during M phase of the cell cycle has been described during both mitosis of mammalian cells (13) and Xenopus oocyte meiosis (11), and hence appears to be a conserved mechanism during cell division. The exception is mammalian eggs, which undergo prolonged Ca 2ϩ oscillations postfertilization and maintain an active SOCE (30).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as is the case in Xenopus eggs, SOCE inactivates during mitosis of mammalian cells (Preston et al, 1991;Tani et al, 2007), arguing that MPF activation typically leads to SOCE inactivation, since mitosis also requires MPF/cdk1. Therefore, mammalian eggs are the exception in terms of maintaining SOCE functional during the division phase of the cell cycle.…”
Section: Store-operated Ca 2r Entry (Soce)mentioning
confidence: 92%
“…We recently observed that, unlike interphase cells, the depletion of intracellular calcium stores with ATP was not followed by SOCE in mitotic cells which indicates the inhibition of this vital [Ca 2+ ]i -regulating mechanism. A few reports have implied either a down-regulation or a complete absence of SOCE in mitotic cells presumably due to uncoupling between cell surface channels and the ER (Volpi and Berlin, 1988;Preston et al, 1991;Tani et al, 2007). However, no attempts have been made to substantiate these findings and possibly shed some light on the cellular mechanisms involved.…”
Section: Laser Scanning Confocal Microscopy To Monitor [Ca 2+ ]I D Y mentioning
confidence: 99%